2016
DOI: 10.3390/ijerph13121258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-HT2A Receptor Polymorphisms, Work Stressors, and Social Support on Job Strain among Petroleum Workers in Xinjiang, China

Abstract: Previous studies have shown that work stressors and social support influence job strain. However, few studies have examined the impact of individual differences on job strain. In Xinjiang, there are a large number of petroleum workers in arid deserts. The present study investigated the effects of work stressors, social support, and 5-hydroxytryptamine receptor (5-HTR2A) genotype on the etiology of job strain among petroleum workers in Xinjiang. A cross-sectional study was carried out between January and August… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Hence, the causes of high incidences of anxiety and depression in young ED men might be due to the heavy burden of life and work pressure. Many previous studies have shown that high life and work pressure may have harmful effects on psychological health (Harvey et al, ; Jiang et al, , ; Tao, Zhang, Song, Tang, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the causes of high incidences of anxiety and depression in young ED men might be due to the heavy burden of life and work pressure. Many previous studies have shown that high life and work pressure may have harmful effects on psychological health (Harvey et al, ; Jiang et al, , ; Tao, Zhang, Song, Tang, & Liu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher ORQ scores indicate more demanding tasks, higher PSQ scores indicate higher levels of stress, and higher PRQ scores indicate a stronger ability to respond to occupational stress. By grouping the subjects’ occupational stress according to the PRQ score [40] and the occupational stress norm [41], based on the formula T = 50 + 10 (ΧtrueΧ¯)/s (i.e., where Χ represents each sub-item, Χ¯ is the norm average, and s is the norm standard deviation), the original score of the subscale is converted into the T value. A T value ≥70 is classified as high occupational stress; 60 to 69 points indicate moderate occupational stress; and ≤59 points indicates low occupational stress.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that mental and physical health are affected by natural conditions including the monotonous lifestyle of arid deserts and other harsh environments [ 27 , 28 ]. Due to the socioeconomic impact of occupational stress [ 29 ], the majority of research studies have focused on white-collar workers [ 30 , 31 ] although few studies have examined the relationship between occupational stress, 5-HTR2A polymorphism, and mental health in petroleum workers stationed in arid deserts [ 32 , 33 ]. This research conducted a cross-sectional study of petroleum workers in Xinjiang to investigate: (1) the relationship between occupational stress and mental health; and (2) the relationship between 5-HTR2A polymorphism and mental health.…”
Section: Introductionmentioning
confidence: 99%